Defining a Central Monitoring Capability: Sharing the Experience of TransCelerate BioPharma's Approach, Part 1. (September 2014) - Wilson, Brett; Provencher, Tom; Gough, Jacqueline; Clark, Stephanie; Abdrachitov, Ramil; de Roeck, Karolien; Constantine, Sarah Jane; Knepper, David; Lawton, Andy
Central monitoring, on-site monitoring, and off-site monitoring provide an integrated approach to clinical trial quality management. TransCelerate distinguishes central monitoring from other types of central data review activities and puts it in the context of an overall monitoring strategy. Any organization seeking to implement central monitoring will need people with the right skills, technology options that support a holistic review of study-related information, and adaptable processes. There are different approaches actively being used to implement central monitoring. This article provides a description of how companies are deploying central monitoring, as well as samples of the workflows that illustrate how some have implemented it. The desired outcomes include earlier, more predictive detection of quality issues. This paper describes the initial implementation steps designed to learn what organizational capabilities are necessary.